Definições preliminares para uma classificação das falácias informais - Pereira Neto, Alípio José Viana (2019)
It´s a dissertation whose objective is to understand and criticize the traditional approach of informal fallacies, as well as some of the contributions provided by contemporary accounts. It is intended, therefore, to present a conception of informal fallacy capable of sustaining further classification, so that it can be used as an objective tool for analyzing and evaluating argumentative discourse. We first discuss, in general, the scope of Formal Logic and what are formal fallacies. Subsequently, we present a more detailed characterization of the Informal Logic, in comparison with the notions of Formal Logic and formal fallacy, previously defined. Following this, we present our critique of the standard treatment of informal fallacies, conferred within the competence of Formal Logic, also examining and criticizing the contributions brought by contemporary accounts of Informal Logic. Finally, we reveal our view of the notion of informal fallacy and how it relates to the possibility of its classification.